Preoperative serum von Willebrand factor, E-selectin and tumor necrosis factor-alpha predict early venous outflow dysfunction after finger replantation: Preoperative serum biomarkers and early venous outflow dysfunction - Chen, Feipeng; Wang, Dexin (Journal of Medical Biochemistry, 2026)
Background: Early venous outflow dysfunction is a leading cause of early failure after finger replantation. This study evaluated whether preoperative serum markers of endothelial activation and inflammation can predict early venous outflow dysfunction and developed a serum-based risk model.Methods: This retrospective cohort included 150 patients who underwent finger replantation between January 2022 and October 2025. Peripheral venous blood was collected 2 h before surgery. Serum von Willebrand factor (vWF), intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E-selectin, C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were measured. Early venous outflow dysfunction was defined as venous congestion requiring intervention within 72 h postoperatively. Independent markers were identified using multivariable logistic regression. Model performance was assessed by receiver operating characteristic analysis (AUC with 95% confidence intervals by the DeLong method and between-model comparison by the DeLong test), calibration by the Hosmer–Lemeshow test, and internal validation using bootstrap resampling (200 iterations).Results: All seven biomarkers were higher in cases (n=74) than controls (n=76) (P